Rate of involuntary admission in Dublin South West: a 5-year retrospective review. (20th February 2015) - McManus, S.; McDonnell, B.; Whitty, P.
Abstract : Objective: International figures for involuntary admissions vary widely. Differences in legislation, professionals' ethics and public attitudes towards risk have been known to influence this rate. Comparing involuntary admission rates in different parts of the same country can help control for variability found between international studies. This study assessed the rates of involuntary admissions in the Dublin South West Mental Health Service compared with the rest of Ireland. Methods: We examined the demographic and clinical profiles of all involuntary patients admitted to the acute psychiatric inpatient unit in Tallaght Hospital between 2007 and 2011. We compared the rate of admission in Tallaght with the rest of Ireland. Data gathered included all patients detained on Form 6 and Form 13 (change of status) looking at age, gender, diagnosis and number of patients who had a Mental Health Tribunal. Form 7 (renewal orders) was also examined We calculated the rate per 100 000 population per year of Form 6 admissions, Form 13 and Form 7 (certificate and renewal order by responsible consultant psychiatrist) using figures from the 2006 Census. All data were analysed using SPSS. Results: The rate of involuntary admission in Tallaght Hospital was significantly lower compared with the rest of Ireland (Form 6: t =−11.2; p <0.001, Form 13: t =−3.1; p =0.04, Form 7: t =−13.9; p =0.001). This difference was evident for all methods of involuntary detention and was also the case for Form 7 (renewal orders). Mental Health Tribunals were held for 59% of patients, a rate comparable with earlier findings described in publications, following the introduction of the new Mental Health Act. Conclusions: Rates per 100 000 population were lower in Dublin South West compared with the rest of Ireland. The reasons for this are not clear. Further research comparing similar services in Ireland could explain these findings.